PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL GROUP INVESTIGATION DENGAN ADVANCE ORGANIZER UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN PEMECAHAN MASALAH PADA SISWA SMP - Yeni Puji Astuti (Jurnal Inovasi Penelitian, 2020)
This research aims to develop a learning material of group investigation model with advance organizer to improve learning output and student’s problem solving skills in SMPN 1 Tanjungbumi. This study would be expected to be applied using the several assessing of instruments. The experiment design of the material resources used one group pretest-posttest design. The assessing of instruments consist of lesson plan, BAS, worksheet, observing activity, test (product, process, and psychomotor), and questionnaire. The validity result showed that lesson plan, BAS, and LKS had in feasible category, LP product and LP process had in feasible category. The assessment of BAS and LKS showed that BAS and LKS had in understandable material by students. Learning feasibility of group investigation model with advance organizer is in excellent category. Reliability of students’ activity observation from the lesson plan with the percentage 92,32%. The completeness of product’s indicator with the percentage 83,33%, and the completeness of process’ indicator (problem solving skills) with the percentage 73,33%. The completeness of the individual output product with the percentage 93,33%, the completeness of the individual output process (problem solving skills) with the percentage 93,33%, the completeness of the individual output psikomotor with the percentage 100%, and the completeness of the individual output afektif with the percentage 100%. Group investigation model with advance organizer got positive respond from the students. The difficulties found during this study was group investigation model with advance organizer was a new thing for the students so the teacher should give information about group investigation model with advance organizer for the students.